Correlation of Smoking with Carbon Monoxide Level and Peak Expiratory Flow Rate in High School Students Banda Aceh - Julie Amalliah; Sri Dianova; Ferry Dwi Kurniawan; Teuku Zulfikar; Nurrahmah Yusuf (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2023)
Background: Indonesia has the highest number of adolescent smokers in the world. Carbon monoxide (CO) is a by-product of tobacco smoking and is inhaled into the lungs. A smokerlyzer can monitor its level. Cigarette smoke also causes inflammation that affects airflow in the airways and can be detected by measuring the peak expiratory flow rate (PEFR). This study aims to determine the relationship between smoking and CO levels and PEFR in high school students in Banda Aceh City.Methods: This quantitative study uses an analytical observational approach with a cross-sectional design. This study involved 300 students from five senior high schools in Banda Aceh. The data were analyzed using the Mann-Whitney and Spearman test with a significance value <0.05.Results: CO levels of the smoker students were higher (12.61 ± 3.342 ppm) than nonsmoker students (2.46 ± 0.569 ppm), p=0.000. The average PEFR for smoking students was lower than nonsmokers (61.11 ± 9.163%) than for non-smoking students (78.48 ± 6.804 %), p=0.000. Duration of smoking in smoking students was also strongly associated with CO levels and PEFR (r=+0.749, p=0,000, r=-0.560, p=0.000, respectively).Conclusion: There is a relationship between smoking and CO levels and PEFR in senior high school students in Banda Aceh.